3. Kirgistan – stosunki z sąsiadami w regionie Azji Centralnej .......... 329 - Panasiuk, Paweł (Kirgistan – oblicza transformacji, 2020)
KYRGYZSTAN AS A REGIONAL ACTOR – THE COUNTRY’S RELATIONS WITH ITS CENTRAL ASIAN NEIGHBOURSThis chapter presents relations between Kyrgyzstan and its closest neighbours in the region of post-Soviet Central Asia: Kazakhstan, Tajikistan, Turkmenistan and Uzbekistan, based on press releases and available statistical data. Observation of relations between these countries in the last 10 years shows that, apart from bilateral economic relations and trade, there has been no political integration at the regional level. This is mainly due to distrust between these countries and border conflicts, as well as the phenomenon of Islamic extremism.